Ethnographies of Power : Working Radical Concepts with Gillian Hart. - CHARI, SHARAD. HUNTER, MARK. SAMSON, MELANIE (Book collections on Project MUSE., 2022)
What does it mean to work with radical concepts in our time of rampant inequality, imperial-capitalist plunder, racial/sexual/class violence and ecocide? When concepts from the past seem inadequate, how do scholars and activists concerned with social change decide what concepts to work with or renew? The contributors to Ethnographies of Power address these questions head on. Gillian Hart is a key thinker in radical political economy, geography, development studies, agrarian studies and Gramscian critique of postcolonial capitalism. In Ethnographies of Power each contributor engages her work and applies it to their own field of study. These applied concepts include: 'gendered labour' practices among South African workers, reading 'racial capitalism' through agrarian debates, using 'relational comparison' in an ethnography of schooling across Durban, reworking 'multiple socio-spatial trajectories' in Guatemala's Maya Biosphere Reserve, critiquing the notion of South Africa's 'second economy', revisiting 'development' processes and 'Development' discourses in US military contracting, reconsidering Gramsci's 'conjunctures' geographically, finding divergent 'articulations' in Cape Town land occupations, and exploring 'nationalism' as central to revaluing recyclables at a Soweto landfill. Ethnographies of Power offers an invaluable toolkit for activists and scholars engaged in sharpening their critical concepts for the social and environmental change necessary for our collective future.